Walking speed and balance both improved in older Japanese adults between 1998 and 2018 - Tetsuhiro Kidokoro; Samantha J. Peterson; Hannah K. Reimer; Grant R. Tomkinson (Elsevier, 2021)
Background/objective: Physical function, the ability of an individual to carry out physical tasks, is meaningfully related to health among older adults. Few studies have analyzed temporal trends in objective performance measures of physical function for older adults. The aim of this study was to estimate temporal trends in balance and walking speed for older Japanese adults (aged 65-79 years) between 1998 and 2018. Methods: Annual, cross-sectional, national fitness surveillance data for balance (n = 114,785) and walking speed (n = 112,289) were reported descriptively by the Japanese Ministry of Education, Culture, Sports, Science and Technology across the 1998-2018 period. Trends in means were estimated by sample-weighted regression, with trends in variability estimated as the ratio of coefficients of variation. Results: There was a moderate improvement in both mean balance (standardized effect size (ES) change (95% confidence interval (CI)): 0.50 (0.48-0.52)) and mean walking speed (ES change (95%CI): 0.53 (0.51-0.55)). Improvements were seen in all gender and age groups, with small gender-related and negligible age-related temporal differences. Variability declined substantially for both balance (ratio of CVs (95%CI): 0.77 (0.75-0.79)) and walking speed (ratio of CVs (95%CI): 0.87 (0.85-0.89)). Conclusion: Improved physical performance is suggestive of a corresponding improvement in health. Declines in variability indicate that temporal improvements were not uniform across the distribution.